Porositas Beton Blended Abu Terbang (Fly Ash) Sebagai Substitusi Semen Di Air Gambut - Mardiah, Ramona; Kamaldi, Alfian; Olivia, Monita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
One of the environmental conditions that can affect the quality of concrete is peat water. In this study an alternative was carried out to improve the durability of concrete in peat environments using pozzolanic material, one of them is fly ash. Fly ash has pozzolanic properties with fine particle size and can react with lime and water so as to produce material that has binding ability. This research studied the porosity of Ordinary Portland Cement (OPC) containing 25% of fly ash immersed in peat water. Fly ash was used as a cement substitutive. The cylinder concrete strength of the specimen at 28 days were 15, 21 and 29 MPa. The specimens were cured first in fresh water for 28 days and then they were immersed in peat water for 7 and 28 days. The porosity of OPC-FA-15, OPC-FA-21, and OPC-FA-29 immersed in peat water for 28 days were 16.10%, 12.16%, and 11.62% lower than that of immersed in fresh water. Moreover, higher concrete quality would result lower porosity value. Based on the results of the tests it is concluded that the replacement of 25% cement by fly ash for the three concrete grades has better physical properties with immersion in peat water. Keywords : Concrete, fly ash, peat water, porosity